Jasmonate signaling in the field, part I: elicited changes in Jasmonate pools of transgenic Nicotiana attenuata populations - Gaquerel, Emmanuel; Stitz, Michael; Kallenbach, Mario; Baldwin, Ian T. (Jasmonate Signaling, 2013)
Nicotiana attenuata, a wild tobacco species native of the southwestern USA that grows in the immediate postfire environment, is one of the important host plants for herbivore populations recolonizing recently burned habitats in the Great Basin Desert. Based on more than 20 years of field research on this eco-genomics model system established in our group, we have developed a genetic and analytical toolbox that allows us to assess the importance of particular genes and metabolites for the survival of this plant in its native habitat. This toolbox has been extensively applied to study the activation of jasmonate signaling after the attack of different herbivore species. Here, we provide detailed guidelines for the analysis, under field conditions, of induced changes in jasmonate pools during insect herbivory. The procedures range from selection and field release of well-characterized transgenic lines for testing the physiological consequences of manipulating jasmonate biogenesis, metabolism, or perception to the metabolic elicitation of chewing herbivore attack and the quantification of the resulting changes in jasmonate fluxes.